1992
DOI: 10.1029/91jd01968
|View full text |Cite
|
Sign up to set email alerts
|

Summertime photochemistry of the troposphere at high northern latitudes

Abstract: The budgets of O3, NOx (NO+NO2), reactive nitrogen (NOy), and acetic acid in the 0–6 km column over western Alaska in summer are examined by photochemical modeling of aircraft and ground‐based measurements from the Arctic Boundary Layer Expedition (ABLE 3A). It is found that concentrations of O3 in the region are regulated mainly by input from the stratosphere, and losses of comparable magnitude from photochemistry and deposition. The concentrations of NOx (10–50 ppt) are sufficiently high to slow down O3 phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
94
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 45 publications
10
94
0
Order By: Relevance
“…Figure 4 shows that the PAN/NO y ratio increases with age in both passes, while the NO x /NO y ratio decreases. These observations of rapid PAN formation confirm the model result of Jacob et al (1992), which showed PAN/NO y in a boreal smoke plume increasing to about 30% in 3 hours. However, the model of Alvarado and Prinn (2009), which simulated the Alaskan fire plume sampled by Goode et al (2000), showed a PAN/NO y ratio of only 4% after 3 h. The key difference between the cases appears to be the emission ratio of NO x in the smoke plumes, which has a large effect on the modeled fractionation of NO y in the smoke plumes.…”
Section: Rapid Formation Of Pan In the Lake Mckay Fire Plumessupporting
confidence: 78%
“…Figure 4 shows that the PAN/NO y ratio increases with age in both passes, while the NO x /NO y ratio decreases. These observations of rapid PAN formation confirm the model result of Jacob et al (1992), which showed PAN/NO y in a boreal smoke plume increasing to about 30% in 3 hours. However, the model of Alvarado and Prinn (2009), which simulated the Alaskan fire plume sampled by Goode et al (2000), showed a PAN/NO y ratio of only 4% after 3 h. The key difference between the cases appears to be the emission ratio of NO x in the smoke plumes, which has a large effect on the modeled fractionation of NO y in the smoke plumes.…”
Section: Rapid Formation Of Pan In the Lake Mckay Fire Plumessupporting
confidence: 78%
“…However, global modelling studies (e.g. Wang et al, 1998) show that surface OH concentrations in higher southern latitudes in January can be lower by a factor of 2}4 compared to northern mid-latitudes where PAN decay rates are comparable to NO V destruction rates (Jacob et al, 1992). Taking into account these uncertainties in the OH mixing ratios during the campaign, the calculation of the NO V destruction of 0.7 pptv h\ is only a rough estimate.…”
Section: Pan Lifetimesmentioning
confidence: 99%
“…Further modelling studies have shown that these NO V production rates were su$cient to establish NO V mixing ratios of less than 10 pptv. Observations made in the middle to lower summertime troposphere over Alaska have indicated that under certain conditions the thermal decomposition of PAN alone could account for the concurrent measured NO V abundance in the lower 6-km tropospheric column (Singh et al, 1992b), whereas in other cases the middle tropospheric (4}6 km) abundance of NO V may have been controlled by the degradation of other organic nitrates due to photolysis or reaction with OH (Jacob et al, 1992).…”
Section: Pan Lifetimesmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary NO x emissions from biomass burning are rapidly converted to PAN within biomass burning plumes [12,37]. Satellite retrievals of PAN could provide substantial information on the fate of NO x emitted by biomass burning in the atmosphere and the impact of these NO x emissions on global tropospheric ozone.…”
Section: Introductionmentioning
confidence: 99%